KUALITAS PELAYANAN SISTEM PENYEDIAAN AIR MINUM (SPAM) DI KABUPATEN SIAK - Sondria, Sintary; Yuliani, Febri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The quality of a service will provide a comfort for the community if it is comply applicable with the standards so that it can increase community satisfaction. The main task of the UPTD Drinking Water Supply System is to manage the facilities and infrastructure of the system in order to provide services to meet the needs of good drinking water to the community in accordance with prevailing laws and regulations. The purpose of this study was to determine the quality of service and the factors inhibiting of the quality of service of the Drinking Water Supply System in Siak Regency. The theoretical concept in this research uses the theory from Lenvine (Sabbarudin, 2015) such as: responsiveness, responsibility and accountability. This research using qualitative methods with a phenomenological approach by using purposive sampling method with techniques such as: data collection interviews, observation, and documentation. The results of this research indicate that the service quality of the Drinking Water Supply System in Siak Regency is still not optimal because there are still sub-districts that have not been reached by the pipeline network of the UPTD of Drinking Water Supply System in Siak Regency. This is what makes the quality of this service not yet reach excellent service quality. The factors inhibiting are the lack of training on the ability of officers and the availability of insufficient tools.Â Keywords: Service Quality, System, Drinking Water